EFFECT OF VITAMIN D DEFICIENCY IN PREGNANT WOMEN - Hamad, Sadiq Nazim Abdel Amir; Aswad, Sarah Ibrahim Mutar; Al-Qadisiyah, Hawraa Ayed Halil Khanzeer; Yahya, Alina Shahab Qahtan; Ali, Mohammed Jassim Mohammed (PT. Antis International Publisher, 2024)
Vitamin D deficiency (VDD) in pregnant women and their children is an important health problem with severe consequences for the health of both. Thus, the objectives of this review were to reassess the magnitude and consequences of VDD during pregnancy, lactation and infancy, associated risk factors, prevention methods, and to explore epigenetic mechanisms in early fetal life capable of explaining many of the non-skeletal benefits of vitamin D (ViD)..